Development of a TaqMan-based triplex qPCR assay for the simultaneous detection of Muscovy reovirus, novel duck reovirus, and Riemerella anatipestifer - Gan, Zhihanlin; Cai, Gaofeng; Li, Haiqin; Zheng, Zhanhong; Song, Linjie; Zhang, Yiyang; Liu, Ping; Chen, Yiwen; Shen, Zhixuan; Gao, Xiaona; Guo, Xiaoquan (Frontiers in Veterinary Science, 2026)
IntroductionIn duck breeding production, the incidence of infection of Riemerella anatipestifer (RA), Muscovy duck reovirus (MDRV), and novel duck reovirus (NDRV) is gradually increasing. Because the clinical symptoms caused by these three pathogens are relatively similar, it is quite difficult to distinguish and diagnose.MethodsThis study aims to establish a TaqMan-based triplex qPCR detection assay that can detect the above three pathogens at the same time. Specifically designed, optimized and verified specific primers and probes, targeting the dtxr gene of RA and the σB protein coding gene of MDRV and NDRV, respectively.ResultsThe results show that the assay has good specificity, sensitivity and stability. The linear detection range of the three pathogens is 102~109 copies/μL and the minimum detection limit can reach 101copies. In this study, 99 clinical on-site samples were tested, and positive samples were detected. In addition, through the analysis of the drug-resistant gene spectrum of the RA isolate, it was found that it carries aminoglycosides (RanA, RanB, aadS), macrocyclic esters [EreD, Erm(35), ErmF], chloramphenicol (floR) and tetracyclines [Tet(X3), Tet(X6), TetX] drug resistance genes of antibacterial drugs.DiscussionIn summary, the TaqMan-based triplex qPCR detection assay established in this study can be used as a fast, sensitive and reliable technical means for large-scale monitoring of RA, MDRV and NDRV infection; at the same time, the analysis of the supporting drug-resistant gene detection assay can provide reference for the rational use of antibacterial drugs in duck breeding production. Test the basis, and then help the breeding link to take scientific and effective prevention and control intervention measures in a timely manner.